2018
DOI: 10.1007/s11136-018-1982-5
|View full text |Cite
|
Sign up to set email alerts
|

Modification of existing patient-reported outcome measures: qualitative development of the MD Anderson Symptom Inventory for malignant pleural mesothelioma (MDASI-MPM)

Abstract: The MDASI-MPM has established content validity and, with the addition of one symptom item, is ready for psychometric testing as fit-for-purpose for a clinical trial of an investigational agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…The results showed that within 7 days after surgery, symptom severity changed dramatically, which was consistent with the original study's ndings (6). Professionals should conduct effective symptom management based on patient-reported outcomes to improve their quality of life and outcomes ( [x], [xi]).…”
Section: Discussionsupporting
confidence: 75%
“…The results showed that within 7 days after surgery, symptom severity changed dramatically, which was consistent with the original study's ndings (6). Professionals should conduct effective symptom management based on patient-reported outcomes to improve their quality of life and outcomes ( [x], [xi]).…”
Section: Discussionsupporting
confidence: 75%
“…In this study, we tested a provisional MPM-specific version of the MD Anderson Symptom Inventory adapted to encompass major symptoms reported by patients with MPM over the duration of treatment. We adopted all of the MDASI-MPM items for psychometric testing on the basis of qualitative interviewing results that established the importance of each item [2]. This psychometric testing is a necessary step in the validation dossier of the MDASI-MPM.…”
Section: Discussionmentioning
confidence: 99%
“…The general principles expressed in the FDA’s guidance on the use of PROs in labeling claims [4] also recommends psychometric evaluation of the items and subscales in an early-phase study [2]. One of the criteria set forth in the FDA guidance is that a PRO instrument must be able to detect change over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations